2003
DOI: 10.1177/1120672103013009-1011
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure, Quality of Block, and Degree of Pain Associated with Ropivacaine in Peribulbar Block: A Comparative Randomized Study with Bupivacaine-Lidocaine Mixture

Abstract: Ropivacaine used in peribulbar block is better than bupivacaine-lidocaine mixture under the same standard conditions in terms of reducing intraocular pressure and postoperative pain in intraocular surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 14 publications
0
14
0
3
Order By: Relevance
“…There were no significant differences in the IOP levels between the groups, even though the IOP was decreased significantly below baseline values at 10 min in the ropivacaine group. It has been reported that the vasoconstrictive effect of ropivacaine leads to a decrease in the intraocular blood volume and that this might play a role in the observed decrease in the IOP (Nakamura et al 1993;Ishiyama et al 1997;Nociti et al 2001;Ozcan et al 2003). In addition, the IOP might have been decreased in the ropivacaine group because the diffusion of ropivacaine through the tissues may be faster than that of lidocaine.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…There were no significant differences in the IOP levels between the groups, even though the IOP was decreased significantly below baseline values at 10 min in the ropivacaine group. It has been reported that the vasoconstrictive effect of ropivacaine leads to a decrease in the intraocular blood volume and that this might play a role in the observed decrease in the IOP (Nakamura et al 1993;Ishiyama et al 1997;Nociti et al 2001;Ozcan et al 2003). In addition, the IOP might have been decreased in the ropivacaine group because the diffusion of ropivacaine through the tissues may be faster than that of lidocaine.…”
Section: Discussionmentioning
confidence: 90%
“…Evidence suggests that ropivacaine has a higher threshold for cardiovascular and central nervous system toxicity than does bupivacaine and a lower threshold than does lidocaine (Arlock 1988;Feldman et al 1989). In addition, the quality of the motor block, the duration of analgesia, and the pain of injection induced by ropivacaine used in peribulbar anesthesia were superior to those observed with other anesthetics (Luchetti et al 2000;Ozcan et al 2003). It has been shown that adrenaline does not increase the efficacy of ropivacaine owing to the inherent vasoconstrictive properties of ropivacaine (Cederholm et al 1992).…”
Section: Methodsmentioning
confidence: 91%
See 3 more Smart Citations